Karakteristik Petani Padi Kecamatan Tonra dan Implikasinya terhadap Penyusunan Programa Penyuluhan Pertanian - Mukarramatul Amriani; Syamsinar Syamsinar; Sulfiana Sulfiana (Jurnal Riset Rumpun Ilmu Tanaman, 2025)
Rice production remains a strategic component in supporting local food security, yet its performance is strongly influenced by the heterogeneity of farmers' characteristics. This study aims to describe the characteristics of rice farmers in Tonra District and analyze their implications for the formulation of agricultural extension programs. Using a descriptive quantitative approach with 100 respondents selected proportionally from eleven villages, the research examines key variables including land size, seed use, fertilizer application, age, education level, and farming experience. The findings reveal clear variations in productivity among farmers, where higher production is generally associated with larger landholding, optimal input use, productive age groups, higher educational attainment, and moderate farming experience. These patterns highlight how farmers' demographic and agronomic characteristics shape their management capacity and adoption of recommended practices. The study emphasizes that extension programs must be designed based on farmers’ actual profiles to enhance relevance and effectiveness. Tailored strategies—such as visual communication for low-education groups, mechanization support for senior farmers, and input-use optimization training—are necessary to improve productivity outcomes. The results provide an important basis for developing more targeted, responsive, and sustainable agricultural extension programming at the district level.